96.0k views
3 votes
Simplify each expression. (10x^3y^2/5x^-3y^4)^-3

2 Answers

2 votes

When a base with an exponent is divided by a base with an exponent, you subtract the exponents together. (But you can only combine the exponents when the bases are the same)

For example:


(x^5)/(x^3)=x^((5-3))=x^2


(x^3)/(y^6) (can't combine the exponents because they have different bases of x and y)


(5^3)/(5^1) =5^((3-1))=5^2=25

When you multiply an exponent directly to a fraction or a base with an exponent, you multiply the exponents together for each base.

For example:


(x^4)^2=x^((4*2))=x^8


(w^2s^3)^5=w^((2*5))s^((3*5))=w^(10)s^(15) (multiply the exponent to each base, w and s)


((x^3)/(y^2))^2=(x^((3*2)))/(y^((2*2))) =(x^6)/(y^4) (multiply the exponent to each base/top and bottom of the fraction)

When you have a negative exponent, you move the base with the negative exponent to the other side of the fraction to make the exponent positive.

For example:


x^(-2) or
(x^(-2))/(1) =(1)/(x^2)


(1)/(2y^(-3)) or
(1)/(2^1y^(-3)) =(y^3)/(2)


((10x^3y^2)/(5x^(-3)y^4) )^(-3) First simplify the fraction inside the parentheses


((10)/(5) *x^((3-(-3)))*y^((2-4)))^(-3)


(2*x^6*y^(-2))^(-3) Now multiply the exponents by -3


2^((1*(-3)))*x^((6*(-3)))*y^((-2*(-3)))


2^(-3)x^(-18)y^6 Make all the exponents positive


(y^6)/(2^3x^(18)) Simplify 2³


(y^6)/(8x^(18)) [y^6 ÷ 8x^(18)]

User Numabyte
by
4.8k points
1 vote

Answer:

y^6/8x^18

Explanation:

Just got it right on Edge2020.

User AbsoluteSith
by
4.2k points